2022
DOI: 10.1021/acs.jafc.2c01365
|View full text |Cite
|
Sign up to set email alerts
|

Current Advances in Structure–Function Relationships and Dose-Dependent Effects of Human Milk Oligosaccharides

Abstract: HMOs (human milk oligosaccharides) are the third most important nutrient in breast milk. As complex glycans, HMOs play an important role in regulating neonatal intestinal immunity, resisting viral and bacterial infections, displaying antiinflammatory characteristics, and promoting brain development. Although there have been some previous reports of HMOs, a detailed literature review summarizing the structure−activity relationships and dose-dependent effects of HMOs is lacking. Hence, after introducing the stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 239 publications
1
7
0
Order By: Relevance
“…In terms of nongenetic factors, the stage of milk maturation is one of the most important influencing factors. Previous studies have reported that the total concentration of HMOs in mature milk was approximately 5-20 g/L [34][35][36][37][38]. In our study, the mean of total concentration of HMOs was consistent with previous reports.…”
Section: Hmos Concentrationssupporting
confidence: 92%
“…In terms of nongenetic factors, the stage of milk maturation is one of the most important influencing factors. Previous studies have reported that the total concentration of HMOs in mature milk was approximately 5-20 g/L [34][35][36][37][38]. In our study, the mean of total concentration of HMOs was consistent with previous reports.…”
Section: Hmos Concentrationssupporting
confidence: 92%
“…Furthermore, in germ-free mice orally fed with 13 C-labeled 2´-FL, the 13 C bolus remains in the intestinal content and was expelled via the feces, indicating that gut microbial metabolites of 2´-FL or Fuc could be responsible for the observed effects since 13 C enrichment of brain tissue occurred when the 13 C-2´-FL or 13 C-Fuc bolus had reached the lower gut containing microbiota (28,29). In this context, it is wellknown that bifidobacteria were able to utilize fucosylated HMOs to produce metabolites such as short-chain fatty acids (e.g., acetate) and lactate (72)(73)(74). During breastfeeding, B. longum ssp.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Previous studies found that 2′-FL modulated the gut microbiota in a structure-dependent manner. 19 2′-FL binds with histo-blood group antigens (HBGAs) or soluble receptors on the intestinal epithelium to recognize or prevent pathogenic bacteria and parasites as an antiadhesive antimicrobial and pathogen decoy receptor. On the other hand, probiotics dominate the infant gut microbiota during breastfeeding via producing transport proteins and intracellular/extracellular glycosidase, which directly participate in the utilization of 2′-FL.…”
Section: Introductionmentioning
confidence: 99%